Status gizi, asupan energi, dan serat sebagai faktor risiko kardiometabolik pada remaja pendek - Siti Nur Fatimah; Ambrosius Purba; Kusnandi Rusmil; Gaga Irawan Nugraha (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: Prevalence of stunted adolescents is important because related with the cardiometabolic risk factor. Control of risk factors reduces the comorbidity including body mass index (BMI) control. Improvement of environmental factors such as energy and fiber intake contribute to reducing disease risk. Objective: This study aimed to analyze the relationship of a stunted adolescent with BMI, energy and fiber intake. Method: This study used cross-sectional design. The subject consisted of early adolescents with 10 to 14 years old in Jatinangor district, West Java. Determination of short stature and BMI refers to the WHO Growth Chart 2005. Data collection by the measure of height, weight, BMI calculation, and interviewed food intake by 3x24 hour food recall and analyzed with Nutrisurvey program. Statistical analysis by Mann-Whitney U test. Results: A total of 212 participants (106 stunted and 106 non-stunted) were enrolled. The proportion of stunted girls is 58 (54,9%) and stunted boys 48 (45,1%). Average of BMI in stunted is 17,15 (2,59) kg/m2 and 18,38 (3,33) kg/m2 in non-stunted, energy intake is 1.488,83 (513,52)kcal in stunted and 1.704,32 (663,49) in non-stunted, fiber intake is 4,36 (1,18) g in stunted and 4,53 (2,15) g in non stunted. There are significant differences in all variables between stunted and non-stunted with a p value for BMI 0,017, in energy intake 0,034 and fiber intake 0,032. BMI showed the correlation with disease risk. including cardiometabolic diseases in stunting. Energy intake and low fiber in growth age increase the risk of cardiometabolic diseases because in stunting have a low metabolic adaptation in protein synthesis and fat oxidation. Conclusion: The study shows there is a difference between BMI, energy intake and fiber in the stunted adolescent and non-stunted adolescent. Further research needs to analyze another risk fctor and intervention to improve nutrition status and metabolic condition.